To be or not to be phosphorylated: understanding the role of Ebola virus nucleoprotein in the dynamic interplay with the transcriptional activator VP30 and the host phosphatase PP2A-B56 - Lennart Kämper; Ida Kuhl; Melina Vallbracht; Thomas Hoenen; Uwe Linne; Axel Weber; Petr Chlanda; Michael Kracht; Nadine Biedenkopf (Emerging Microbes and Infections)
Ebola virus (EBOV) transcription is essentially regulated via dynamic dephosphorylation of its viral transcription activator VP30 by the host phosphatase PP2A. The nucleoprotein NP has emerged as a third key player in the regulation of this process by recruiting both the regulatory subunit B56 of PP2A and its substrate VP30 to initiate VP30 dephosphorylation and hence viral transcription. Both binding sites are located in close proximity to each other in NP’s C-terminal-disordered region. This study investigates NP’s role in VP30 dephosphorylation and transcription activation, focussing on the spatial requirements of NP’s binding sites. Increasing the distance between PP2A-B56 and VP30 at the NP interface revealed that close spatial and orientational contact is necessary for efficient VP30 dephosphorylation and viral transcription. Longer distances were lethal for recombinant EBOV except when a compensatory mutation, NP-T603I, occurred. This mutation, located between the NP binding sites for PP2A-B56 and VP30, fully restored functionality. Mass spectrometry showed that T603 is phosphorylated in recEBOV-NPwt virions. Mutational analysis indicated that T603I facilitates VP30 dephosphorylation in otherwise lethal recEBOV and that dynamic phosphorylation of NP-T603 is important for efficient primary viral transcription in the WT context. These findings emphasize the critical and evolutionarily pressured interplay between VP30 and PP2A-B56 within the NP C-terminal-disordered region and highlight the important role of NP on the regulation of viral transcription during the EBOV life cycle.